Referenciação e construção de sentidos em contos de Clarice Lispector - Mirabile, Luciana (2007)
This dissertation is set in the Reading and Writing research line and its purpose is to study the importance of the reference strategies for the construction of meanings in the text. We intend to evidence, through the analysis of two short stories, the importance of the reference process for the construction of meanings of a text. The aim of this project is to contribute to the Portuguese Language studies, especially to reading. Our specific purposes are: 1. to verify how the reference strategies occur in Clarice Lispector s short stories Os laços de família e Feliz aniversário; 2. to reflect about how the reference process can help the reader in the construction of meanings of the literary short stories. The theoretical basis is in the Text Linguistics and, in order to reach our goals, we sought authors who deal with reference, like Mondada and Dubois (1995, 2003), Koch (2004a), Koch and Elias (2006), et al. The reference strategies were discussed according to Apothéloz and Reichler-Béguelin (1995). We similarly discuss the reading according to Koch (2005b) and Koch and Elias (2006). Concerning to short stories, our project is based on the studies of Moisés (1967), Gotlib (1988), Propp (1983) and Jolles (1976). The results obtained from the short stories analysis showed that the reference process can help the reader construct meanings in the texts he reads, since such process makes the reader construct cohesive chains of meaning. We understand that our research opens new perspectives of reference study in other kinds of texts and for the teaching of reading in last grades of Primary Education